Improving Students' Critical Thinking Through Blended Learning Media Learning Game Word Wall - Ayustyaningtias, Rochma; Alinurdin, Enjang; Wahyudin, Asep (Bumi Publikasi Nusantara, 2025)
This study measured students' critical thinking in informatics subjects using the Word Wall Game. With the rapid advancement of technology in the digital era of 4.0 and 5.0, education is also evolving, supported by various online and offline learning materials. Blended learning, particularly the flex model, is an effective strategy in this digital age. This research employed the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model with a One-Group Pretest-Posttest Design. The results show that the Word Wall Game, integrated with blended learning, enhances interactive learning and significantly improves students' critical thinking by 46.67%. Students' responses to the Word Wall Game were highly positive, with an 86% approval rate in the Technology Acceptance Model (TAM) for the material. This study highlights how innovative learning media can foster creative, effective, and enjoyable learning experiences.